HUBUNGAN ANTARA LINGKUNGAN KERJA DENGAN DISIPLIN GURU PAUD DI KECAMATAN BUKIT RAYA PEKANBARU - Nuraini, Seprina; Zulkifli N, Zulkifli N; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract The purpose of this study was to determine the relationship between early childhood teachers working within Sub district Bukit Raya Pekanbaru. Variables of this study consists of two variables namely the range of work and discipline . The samples used in this study of 52 people. As data collection technique that is used by a survey in the form of Likert scale. To test the validity and reliability using SPSS 17. In the present study proposed the hypothesis that there is a strong and significant relationship between work environment and teachers discipline . From the research results obtained are strong and significant relations between work environment and teacher of early childhood education disciplinein sub district Bukit Raya Pekanbaru. It can be known from the results of the analysis of data obtained taker thitung value = 6.66 while the ttabel ( 5 % ) (dk = n -2 = 52-2 = 50) until ttabel = 2.39 . Because thitung greater than ttabel or 6.66 > 2.39 so that may mean that there is a strong and significant correlation between the range of disciplines work with teachers . The coefficient determinant produced is r2 = 47% with P = 0.000 ( P <0.05), it can be seen that the work environment as much as 47% influence on the discipline teacher. Keywords: work environment, the teacher of early childhood education discipline